A spontaneous ruptured intracranial dermoid cyst in an older patient - Kotan, Dilcan; Sayan, Saadet; Polat, Pınar; Özözen Ayas, Zeynep (Wolters Kluwer Health, 2015)
Dermoid cysts are rare cystic tumors originating from ectodermic cells within the intracranial region. These cysts emerge during closure of the neural tube during embryological development. The symptoms are generally incidental and nonspecific. If rupture occurs, the cyst contents propagate through the subarachnoid space and the ventricular system. The dramatic appearance of subarachnoid and cisternal fat droplets facilitates the diagnosis of dermoid cyst rupture by computer tomography and magnetic resonance imaging. Herein, we present a case of ruptured dermoid cyst in an elderly patient. The patient presented with minor symptoms such as nonspecific headache and dizziness; dermoid cyst rupture was diagnosed by observing the fat droplets disseminate into the subarachnoid and cisternal spaces that extend from the left cerebellopontine angle, adjacent to the left carotid channel, to the cavernous sinus, using computer tomography and magnetic resonance imaging.
Keywords: Dermoid Cyst; Rupture; CT; MRI